Dynamics analysis of the set of trajectories on a product of convex compacts - Martynyuk, A. A.; Chernetskaya, L. M.; Martynyuk-Chernienko, Yu. A. (Reports of the National Academy of Sciences of Ukraine, 2016)
For a set of differential equations with Hukuhara derivative defined on a product of nonempty convex and compact spaces, the comparison principle and sufficient conditions of stability of a stationary motion are established. We use the vector Lyapunov-like function of a special structure.